2013
DOI: 10.1002/ange.201302675
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐ and Achiral‐Guest‐Triggered Chiral Inversion in a Planar Chiral pseudo[1]Catenane

Abstract: Chiral inversion systems have received a great deal of interest because they offer new applications in chemical sensing, enantioselective catalysis, and in the chirality switching of liquid crystals and photoluminescence. [1] However, chiral inversion has only been demonstrated in a few artificial molecules, such as helical oligomers and polymers [2,3] and axially chiral compounds. [4] In the present study, we present a new chiral inversion system, triggered by achiral guests and solvents, in a novel artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 41 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…However, the distinctive behavior of fluorescence responses of 1 to 2 in these solvents is attributed to different solvent-effect parameters including the extent of favorable hydrogen bonding and solute–solvent π–π stacking interactions. 6 Comparatively, more polar halogenated solvents such as chloroform gave a rather weak recognition for R , R - 2 with an ef value of only 1.29, whereas in highly polar protic solvents such as methanol, no detectable chiral recognition was observed. By contrast, polar aprotic solvents, such as acetonitrile, showed a moderate sensing ability with an ef of 1.55 for R , R - 2 with emission shifted at a longer wavelength of 405 nm.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the distinctive behavior of fluorescence responses of 1 to 2 in these solvents is attributed to different solvent-effect parameters including the extent of favorable hydrogen bonding and solute–solvent π–π stacking interactions. 6 Comparatively, more polar halogenated solvents such as chloroform gave a rather weak recognition for R , R - 2 with an ef value of only 1.29, whereas in highly polar protic solvents such as methanol, no detectable chiral recognition was observed. By contrast, polar aprotic solvents, such as acetonitrile, showed a moderate sensing ability with an ef of 1.55 for R , R - 2 with emission shifted at a longer wavelength of 405 nm.…”
Section: Resultsmentioning
confidence: 97%
“…This solvent-dependent opposite trend in the CD spectrum can be attributed only to the conformational changes occurring in different solvents. 6 Thus, it is concluded that this solvent-dependent switching to a specific stereodynamic conformational feature is responsible for the inversion of chiral recognition observed in fluorescence as helicity also plays a key role in controlling the enantiomer recognition of 2 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The inhibition of the oxygen-through-annulus rotation will lead to a pair of planar-chiral enantiomers. Three approaches, including rotaxanation, the introduction of a side ring into one ring unit, as well as the chemical modification of bulky groups onto the rims, have been exploited for constructing chiral pillar [5]arenes [18][19][20]. Bulky groups, such as cyclohexylmethyl, phenyl, of bulky groups onto the rims, have been exploited for constructing chiral pillar [5]arenes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Three approaches, including rotaxanation, the introduction of a side ring into one ring unit, as well as the chemical modification of bulky groups onto the rims, have been exploited for constructing chiral pillar [5]arenes [18][19][20]. Bulky groups, such as cyclohexylmethyl, phenyl, of bulky groups onto the rims, have been exploited for constructing chiral pillar [5]arenes [18][19][20]. Bulky groups, such as cyclohexylmethyl, phenyl, or bithienyl groups, have been chemically grafted onto one or more hydroquinone ether units, and the oxygen-through-annulus rotation was restrained or completely stopped [21,22].…”
Section: Introductionmentioning
confidence: 99%